Anisotropic bianchi type-ii modified holographic ricci dark energy model in scale-covariant theory of gravitation - Ram S.; Chandel S.; Verma M.K. (My University, 2025)
In this paper, we obtain an anisotropic Bianchi type-II space–time with dark matter and modified holographic Ricci dark energy in the scale-covariant theory of gravitation. Exact solutions of the field equations are obtained by assuming (i) a negative constant value of the deceleration parameter, (ii) the component s11of the shear tensor s ji is proportional to the mean Hubble parameter, and (iii) the gauge function f is proportional to a power function of the average scale factor. We have also discussed some important physical aspects of the model, which is in agreement with the modern cosmological observations. © 2021 The Author(s).